Formation of material prescribed phase composition from refractory filler silica powder modified with alkoxide and sol-gel composite - Semchenko, G. D.; Shuteeva, I. Yu.; Ryshchenko, M. I.; Borisenko, O. N. (Kluwer Academic/Plenum Publishers, USA, 2014)
Creation of ceramics and refractories with improved physicomechanical properties is possible with use of nanomaterials in their technology. Introduction of SiC nanoparticles into a ceramic material charge by using modified filler powders is proposed. Fillers modified with tetraethoxysilane during grinding leads to powder crystal structure breakdown and SiC mechanochemical synthesis. The amount of -SiC synthesized in this way depends on the amount of modifying additive. Results are provided for modified filler phase composition before and after heat treatment at 1000°C, and mechanochemically synthesized SiC thermal stability is established. It is shown that sintering of modified electro-corundum worsens with an increase in amount of synthesized silicon carbide nanoparticles. The difference is demonstrated in phase composition formation with heat treatment of a mixture of modified and normal finely ground electrocorundum with a sol-gel binder and firing up to 1600°C. Silicon carbide nanoparticle synthesis does not exceed 3 – 7 % in both cases. Recommendations are given for use of corundum filler with a different amount of modifying additive.
Keywords: filler; modification; tetraethoxysilane; synthesis; powder sintering; phase composition; β-SiC nanoparticles